Mempersiapkan Warga Belajar STIT Raden Wijaya Mojokerto dalam Era Disruptions dengan Motto Toward Excellence As Integrated Education untuk Mengatasi Isu Kebangkrutan Perguruan Tinggi Secara Umum - Mohammad Badru Tamam (PROGRESSA: Journal of Islamic Religious Instruction, 2018)
The internet and its ability to provide faster and more extensive ways to access content are the main drivers of disruption in this story. This allows the aggregation and sorting of content and the dissemination of content to groups of people larger than is possible through previous forms of distribution. The researcher formulated a study on how to prepare the learning citizens of STIT Raden Wijaya Mojokerto in the era of disruptions with the motto toward excellence as integrated education ?. This research is "Online Library Research". The research data used is secondary data. Data collection techniques used by the authors in this study are documentation aimed at the subject of research, but study the available documents. From the results of the discussion it can be concluded that by holding the two main streams of higher education (discovery and assembly), in this case it is more appropriate to integrate the STIT Raden Wijaya motto toward excellence as integrated education, so that concerns over the possibility of STIT RAden Wijaya's bankruptcy are not reasoned again. In addition to the existence of STIT RAden Wijaya, it can still be maintained, so that its higher education has been restored to its role as a guide or guide to human civilization, rather than as an impostor of what has been done by the industrial world